2020
DOI: 10.1136/jitc-2020-001681
|View full text |Cite
|
Sign up to set email alerts
|

Eftilagimod alpha, a soluble lymphocyte activation gene-3 (LAG-3) protein plus pembrolizumab in patients with metastatic melanoma

Abstract: BackgroundTo evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of eftilagimod alpha (efti), a soluble lymphocyte activation gene-3 protein, in combination with the programmed cell death-1 (PD-1) antagonist pembrolizumab.MethodsThe study was divided into two parts; parts A and B, where part A was the dose escalation part and part B was an extension part of the study. Patients with metastatic melanoma were treated with efti plus the standard dose of pembrolizumab. Blood samples were assaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 20 publications
(23 reference statements)
0
53
0
3
Order By: Relevance
“…It could be a potential target for combination therapies with PD-1 blockade. Indeed, Woo et al showed that there is a synergistic cooperation between LAG-3 and PD-1 in limiting tumor growth [ 48 ] and, recently, a soluble LAG-3 protein in combination with anti-PD-1 was tested in patients with metastatic melanoma [ 49 ]. Another checkpoint target candidate is CCR4, that plays an important role in regulating the immune balance and is highly expressed in Treg cells.…”
Section: Cd4 T Cells In Immune Checkpoint Blockade (Icb) Therapymentioning
confidence: 99%
“…It could be a potential target for combination therapies with PD-1 blockade. Indeed, Woo et al showed that there is a synergistic cooperation between LAG-3 and PD-1 in limiting tumor growth [ 48 ] and, recently, a soluble LAG-3 protein in combination with anti-PD-1 was tested in patients with metastatic melanoma [ 49 ]. Another checkpoint target candidate is CCR4, that plays an important role in regulating the immune balance and is highly expressed in Treg cells.…”
Section: Cd4 T Cells In Immune Checkpoint Blockade (Icb) Therapymentioning
confidence: 99%
“…A phase 1 study of eftilagimod alpha (IMP321), an antigenpresenting cell (APC) activator for LAG-3, in combination with pembrolizumab was conducted in 24 patients with metastatic melanoma (NCT02676869) (Atkinson et al, 2020). The primary endpoints were the recommended phase 2 dose (RP2D), safety, and tolerability of the combined agents.…”
Section: Clinical Trials On Lag-3mentioning
confidence: 99%
“…Indeed, high levels of sLAG-3 is associated with improved prognosis in patients with gastric cancer and correlates with serum levels of IL-12 and IFNγ [ 263 ]. Harnessing this feature of sLAG-3, clinical trials utilising recombinant sLAG-3 together with ICB have also shown encouraging results in early clinical trials [ 264 , 265 ], highlighting its potential role as a therapeutic adjuvant.…”
Section: Inhibitory Receptorsmentioning
confidence: 99%